Procurement & negotiation practices in ADA – analytics data advertising (Axiata Digital Bangladesh) - Mizan, Meraz Bin (Brac University, 2021)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2021.